Lessons from a geospatial analysis of depot medroxyprogesterone acetate sales by licensed chemical sellers in Ghana. (August 2015) - Shelus, Victoria; Lebetkin, Elena; Keyes, Emily; Mensah, Stephen; Dzasi, Kafui
Abstract: Objectives: To map access to depot medroxyprogesterone acetate (DMPA) from licensed chemical sellers (LCS); to estimate the proportion of women of reproductive age in areas with access; and to examine affordability and variability of costs. Methods: A geospatial analysis was conducted using data collected from 298 women who purchased DMPA from 49 geocoded LCS shops in the Amansie West and Ejisu-Juabeng districts of Ghana from June 4 to August 31, 2012. The women reported on cost and average distance traveled to purchase DMPA. Results: In Amansie West, 21.1% of all women of reproductive age lived within average walking distance and 80.4% lived within average driving distance of an LCS. In Ejisu-Juabeng, 41.9% and 60.1% of women lived within average walking and driving distance, respectively. Distribution of affordability varied across each district. Conclusions: Access to LCS shops is high, and training LCS to administer DMPA would increase access to family planning in Ghana, with associated time and cost savings.